2012
DOI: 10.1007/s00244-012-9749-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Benthic Invertebrate Communities as a Function of Distance from Two Fish-Processing Plant Effluent Discharges in New Brunswick, Canada

Abstract: Benthic invertebrate communities have been known to change due to impacts from nutrient-rich industrial outputs, such as those from pulp and paper, sewage-treatment plants, or aquaculture. Fish-processing plants have been recognized as contributors of large volumes of nutrient rich effluent to marine and estuarine environments, but their effect on benthic invertebrate communities is unknown. Benthic invertebrates and sediment samples were obtained from marine sampling stations at 0-, 10-, 30-, and 100-m distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In these locations, significant differences were also observed in the overall community composition between the receiving water and reference sites (Figure ), with patterns in species composition being best explained by one or more indicators of sediment enrichment (organic content, sediment chlorophyll, and redox depth). Somewhat lower ecological quality (AMBI) values in the receiving water relative to the reference site in the near shore at some locations also indicated that wastewater is affecting benthic communities (Figure ), and differences in index values were generally driven by a higher density of pollution tolerant oligochaete species in the receiving water. , According to the model put forth by Pearson & Rosenburg, (Figure ) these results provide evidence that the benthic invertebrate communities in Grise Fiord, Kugaaruk, Pond Inlet, and Pangnirtung were being mildly enriched by wastewater effluent on the scale of 20–225 m from shore (Figure ).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…In these locations, significant differences were also observed in the overall community composition between the receiving water and reference sites (Figure ), with patterns in species composition being best explained by one or more indicators of sediment enrichment (organic content, sediment chlorophyll, and redox depth). Somewhat lower ecological quality (AMBI) values in the receiving water relative to the reference site in the near shore at some locations also indicated that wastewater is affecting benthic communities (Figure ), and differences in index values were generally driven by a higher density of pollution tolerant oligochaete species in the receiving water. , According to the model put forth by Pearson & Rosenburg, (Figure ) these results provide evidence that the benthic invertebrate communities in Grise Fiord, Kugaaruk, Pond Inlet, and Pangnirtung were being mildly enriched by wastewater effluent on the scale of 20–225 m from shore (Figure ).…”
Section: Resultsmentioning
confidence: 73%
“…Somewhat lower ecological quality (AMBI) values in the receiving water relative to the reference site in the near shore at some locations also indicated that wastewater is affecting benthic communities (Figure 4), and differences in index values were generally driven by a higher density of pollution tolerant oligochaete species in the receiving water. 3,13 According to the model put forth by Pearson & Rosenburg, 3 (Figure 2) these results provide evidence that the benthic invertebrate communities in Grise Fiord, Kugaaruk, Pond Inlet, and Pangnirtung were being mildly enriched by wastewater effluent on the scale of 20−225 m from shore (Figure 2).…”
Section: ■ Results and Discussionmentioning
confidence: 77%
“…The experts identified impacts on salinity, nutrients, temperature, water clarity, sedimentation, and contaminants (Figure 3 ). In the literature, upland development had a negative relationship with salinity (Corcoran et al, 2010 ); a strong positive relationship with nutrients due to industrialized agriculture, urban wastewater, atmospheric deposition, and fish processing plants (Canton et al, 2012 ; Garrido‐Pérez et al, 2002 ; Kim et al, 2015 ; Lalonde & Ernst, 2012 ); and a strong negative relationship with water clarity (Desmond et al, 2015 ). Upland development also had a positive relationship with benthic sedimentation driven by land clearing, mining, poorly handled wastewater, and coal‐fired power plant emissions (González et al, 2014 ; Gorostiaga & Díez, 1996 ); and a strong positive relationship with nearshore contaminants, especially heavy metals and petrochemicals due to current and historical military, industrial, residential, and agricultural effluent (Harris et al, 2011 ; O’Connor, 2002 ; Xu et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…This literature review was designed to evaluate the pathways identified in the focus group's conceptual model, not to seek out any missing pathways; however, during our keyword searches, we did identify four driver‐to‐pressure pathways and two pressure‐to‐kelp pathways that did not fit into the expert‐identified pathways and that may need to be considered going forward. First, the human activity of net‐pen aquaculture was identified in the broader temperate coast literature searches as increasing nearshore contamination, benthic sedimentation, and nutrients; and decreasing water clarity (Claudet & Fraschetti, 2010 ; Feng et al, 2004 ; Lalonde & Ernst, 2012 ; Wang et al, 2020 ). Second, invasive algal species, included under the category of human impacts to trophic structures, may enhance benthic sedimentation rates (Bulleri et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%